2020
DOI: 10.5469/neuroint.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Fluoroscopy Protocol for Diagnostic Cerebral Angiography

Abstract: Purpose: We applied a low-dose fluoroscopic protocol in routine diagnostic cerebral angiography and evaluated the feasibility of the protocol.Materials and Methods: We retrospectively reviewed a total of 60 patients who underwent diagnostic cerebral angiography for various neurovascular diseases from September to November 2019. Routine protocols were used for patients in the first phase and low-dose protocols in the second phase. We compared radiation dose, fluoroscopy time, and complications between groups.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Based on a basic knowledge, there are several factors that affect patient radiation dose during the cerebral angiographic procedure, such as the number of exposures, frame rate, additional filter thickness, focal spot size, number of images, fluoroscopic time, and pulse. Several lines of evidence have demonstrated that optimization through the modification of these factors significantly reduces radiation dose during cerebral angiography [8,10,11,15,16]. Since some factors (number of image and acquisition time) could not be controlled in this study, a statistical analysis of radiation doses from the conventional and high kV techniques using analysis of covariances (ANCOVAs) was necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a basic knowledge, there are several factors that affect patient radiation dose during the cerebral angiographic procedure, such as the number of exposures, frame rate, additional filter thickness, focal spot size, number of images, fluoroscopic time, and pulse. Several lines of evidence have demonstrated that optimization through the modification of these factors significantly reduces radiation dose during cerebral angiography [8,10,11,15,16]. Since some factors (number of image and acquisition time) could not be controlled in this study, a statistical analysis of radiation doses from the conventional and high kV techniques using analysis of covariances (ANCOVAs) was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The high kV technique reduced the 2DA DAP by up to 50.12%. In addition, the median total DAP in the high kV technique group (10,967.55 µGy•m 2 ) decreased from the conventional technique group (16,198.53 µGy•m 2 ) by 32.29%.…”
Section: Effects Of the High Kv Technique On Patient Radiation Dosementioning
confidence: 92%
“…However, as most aneurysms occur in the circle of Willis, the lens is inevitably exposed to radiation in 3D-RA. While many studies in the neurointerventional field have investigated different protocols for reducing radiation doses [ 7 8 9 10 11 12 13 14 15 ], few papers focused on dose reduction in 3D-RA, and none specifically focused on reducing the dose to the lens.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the application of low-dose protocols is effective and safe for diagnostic angiography. Song et al [ 4 ] created a low-dose protocol by gradually decreasing the detector entrance dose from 23 to 8 nGy, which lowered the fluoroscopy dose area product (DAP) and air kerma (AK) by 52% in diagnostic cerebral angiography, as compared to default settings. Also, van der Marel et al [ 5 ] created a dose-reduction platform, and its application reduced cumulative DAP in both diagnostic and neurointervention procedures by 53.2%.…”
mentioning
confidence: 99%